The Importance of Learning English Literacy for Accounting in Higher Education: Benefit and Drawbacks - Samirah Dunakhir; Isnawati Osman (International Journal of Language Education, 2023)
This qualitative research aims to explore the importance of learning English literacy skills for English as a Foreign Language (EFL) accounting students in higher education. The data were collected through in-depth interviews, focus group discussions, and document analysis, and analyzed thematically. The findings indicate that developing English literacy skills offers numerous benefits for EFL accounting students, such as building literacy competence, enhancing employability, improving communication skills, facing globalization, understanding accounting terms and subjects, and identifying errors in accounting. However, the study also identified some drawbacks, time and effort including, Balancing Language Learning with Technical Accounting Skills Development and linguistic difficulties and frustration. The study suggests that educational institutions and policy makers should develop comprehensive strategies that support EFL accounting students in acquiring English literacy skills while addressing the potential challenges they may encounter. These findings have important implications for accounting education, highlighting the need to provide adequate resources and support to EFL accounting students to help them develop their English literacy skills and succeed in their academic and professional pursuits